2013
DOI: 10.5424/sjar/2013111-3113
|View full text |Cite
|
Sign up to set email alerts
|

An approach to costs and energy consumption in private urban Spanish Mediterranean landscapes from a simplified model in sprinkle irrigation

Abstract: The number of private gardens has increased in recent years, creating a more pleasant urban model, but not without having an environmental impact, including increased energy consumption, which is the focus of this study. The estimation of costs and energy consumption for the generic typology of private urban gardens is based on two simplifying assumptions: square geometry with surface areas from 25 to 500 m2 and hydraulic design with a single pipe. In total, eight sprinkler models have been considered, along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Not much information on costs has been found in gardening. As an example, Arbat et al (2013) analyzed nearly 500 private gardens in two Spanish cities, obtaining a range of MOM a costs between 0. and .6 €•m -2 . In the case of The Alcazar, energy only represents 4% of total costs, a very low value considering that Arbat et al (2013) observed a range of 3.5-22.8 % of energy over total costs.…”
Section: Discussionmentioning
confidence: 99%
“…Not much information on costs has been found in gardening. As an example, Arbat et al (2013) analyzed nearly 500 private gardens in two Spanish cities, obtaining a range of MOM a costs between 0. and .6 €•m -2 . In the case of The Alcazar, energy only represents 4% of total costs, a very low value considering that Arbat et al (2013) observed a range of 3.5-22.8 % of energy over total costs.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the management of water distribution networks (WDNs) is increasingly based on use of models as decision support tools, particularly in performance and energy efficiency implications (Rodriguez-Diaz et al, 2010;Arbat et al, 2013;Cabrera et al, 2014). When different database and mathematical algorithms are combined, these hydraulic models are an useful tool to analyze WDNs, if these models are properly calibrated.…”
Section: Introductionmentioning
confidence: 99%
“…All the farm inputs, e.g. fertilizers, chemicals and mechanization infrastructures utilize some forms of energy indirectly for formulation, storage and distribution (Fluck & Baird, 1980;Dyer & Desjardins, 2006;Arbat et al, 2013). Human activities play a key role in total greenhouse gas (GHG) emissions, of which the global food system is responsible for around one third of all (Gilbert, 2012;Houshyar et al, 2012) while cropping systems contribute to 14% of the global net CO 2 emissions (Cooper et al, 2011).…”
Section: Introductionmentioning
confidence: 99%